PREPARATION AND CHARACTERIZATION OF CAESIUM BASED CLAY CATALYST FOR GLYCEROL CONVERSION - ALIAS, NADHIRAH (IRC, 2017)
Caesium based clay catalyst was successfully prepared and well characterized using Xray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Field Emission Scanning Electron Microscope (FESEM), Surface area and pore analyser (SAP) and Thermogravimetric analysis (TGA) techniques. XRD demonstrated the crystallinity, preservation of clay structure and the presence of Caesium. FTIR graph indicated that prepared samples showed vibrational stretch due to the modification of clay with Caesium. The calcined Cs/MK10 was sent to the Surface Area and Pore Analyzer (SAP) to analyze the surface porosity. Surface morphology was studied using Field Emission Scanning Electron Microscope (FESEM). Thermogravimetric analysis (TGA) was done to determine the changes in physical and chemical properties of the catalyst with the function of time and resulted in very low weight loss thus the prepared Caesium based clay catalyst was considered stable. The reactivity of etherification of glycerol over prepared catalyst was done under microwave irradiation instead of conventional way. The effect of microwave irradiation on the reaction is observed and found that the prepared clay catalyst was active for glycerol conversion. The highest conversion was found to be 98% at high level of microwave (800W) within 5 minutes of reaction time. The prepared catalyst is also a good option to convert glycerol into polyglycerol.